Sustained corneal nerve loss predicts the development of diabetic neuropathy in type 2 diabetes - Ponirakis, Georgios; Al-Janahi, Ibrahim; Elgassim, Einas; Homssi, Moayad; Petropoulos, Ioannis N.; Gad, Hoda; Khan, Adnan; Zaghloul, Hadeel B.; Ali, Hamda; Siddique, Mashhood A.; Mohamed, Fatima F. S.; Ahmed, Lina H. M.; et al. (Frontiers in Neuroscience, 2024)
Introduction: This study was undertaken to investigate whether sustained rather than a single measure of corneal nerve loss was associated with the onset of diabetic peripheral neuropathy (DPN) and progression of neuropathic symptoms and deficits in individuals with type 2 diabetes (T2D). Methods: Participants underwent clinical, metabolic testing and assessment of neuropathic symptoms, vibration perception threshold (VPT), sudomotor function, and corneal confocal microscopy (CCM) at baseline and at 1, 2, and 4-7 years. Sustained corneal nerve loss was defined as an abnormal corneal nerve fiber density (CNFD, <24 fibers/mm2), corneal nerve branch density (CNBD, <21 branches/mm2), and corneal nerve fiber length (CNFL, <16 mm/mm2) persisting for ≥50% of the study duration. Results: 107 participants with a mean duration of T2D of 13.3±7.3 years, aged 54.8±8.5 years underwent baseline and follow-up assessments over a median duration of 4 years, range 1-7 years. The DPN prevalence at baseline was 18/107 (16.8%) and of the 89 participants without DPN at baseline, 13 (14.6%) developed DPN during follow-up. Around half of the cohort had sustained corneal nerve damage and corneal nerve measures were significantly lower in this group compared to those without sustained damage (P<0.0001). Sustained corneal nerve damage was associated with the development of DPN (P<0.0001), a progressive loss of vibration perception (P≤0.05), increased incidence of burning pain, numbness, or a combination of both (P=0.01-0.001) and a borderline association with progressive sudomotor dysfunction (P=0.07). Sustained abnormal CNFL effectively distinguished between participants who developed DPN and those who did not (AUC: 76.3%, 95% CI: 65.9-86.8%, P<0.0001), while baseline and other sustained measures did not predict DPN onset. Conclusions: Sustained abnormal CCM is associated with more severe corneal nerve damage, DPN development, and progression of neuropathic symptoms and deficits. Regular CCM monitoring may enable the identification of those at greater risk of developing and worsening DPN who may benefit from more aggressive risk factor reduction.